Implementasi Nilai-Nilai Pancasila Dalam Mengatasi Ketimpangan Keadilan Digital Di Era Teknologi Indonesia - Rahayu, Setyaning; Saputra, Helmi Rizkih; Sunaryo, Sidik (Lex Stricta : Jurnal Ilmu Hukum, 2025)
This study investigates the implementation of Pancasila values in addressing digital justice inequality in Indonesia within the context of the modern technological era. Digital disparities covering unequal access to technology, gaps in digital literacy, and uneven infrastructure development have generated social inequalities that conflict with the fundamental principles of Pancasila, particularly the fifth principle concerning social justice for all Indonesians. Employing a qualitative approach through literature analysis, this research examines how Pancasila can serve as a philosophical foundation for fostering equitable digital justice. The findings demonstrate that Pancasila values may function as an ethical framework for reducing digital inequality through a holistic strategy encompassing equal access to technology, the enhancement of digital literacy grounded in Pancasila values, and the promotion of equitable infrastructure development. This study contributes theoretically to the discourse on technology and Pancasila philosophy while also offering practical recommendations for policymakers in advancing digital justice in Indonesia.